2021
DOI: 10.1177/03091333211030608
|View full text |Cite
|
Sign up to set email alerts
|

Global assessment of wind erosion based on a spatially distributed RWEQ model

Abstract: Wind erosion is a global environmental problem and affects the sustainable use of land soil. The current efforts in wind erosion modeling mainly focus on local scales, yet very few studies have attempted to quantify the soil losses by wind on a large scale. Here, we proposed a distributed version of the revised wind erosion equation model (DRWEQ) to assess the spatial and temporal variations of wind erosion globally. The DRWEQ model used meteorological, soil, topographic, and remote sensing data to simulate gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…According to the United Nations Environment Program, about 1.5 billion people worldwide depend on degraded land; while Africa and Asia account for about 62% of the wind-eroded areas in the world, they also suffer from 91% of the total soil loss (You et al, 2021; Yang et al, 2022). Land degradation caused by soil wind erosion has become a major global challenge for human survival and sustainable development.…”
Section: Discussionmentioning
confidence: 99%
“…According to the United Nations Environment Program, about 1.5 billion people worldwide depend on degraded land; while Africa and Asia account for about 62% of the wind-eroded areas in the world, they also suffer from 91% of the total soil loss (You et al, 2021; Yang et al, 2022). Land degradation caused by soil wind erosion has become a major global challenge for human survival and sustainable development.…”
Section: Discussionmentioning
confidence: 99%
“…For the model structure, the NWESMC and RWEQ belonged to the empirical model, and the WEPS and IWEMS were mechanistic models [ 34 ]. These models were widely used for regional wind erosion evaluation in the arid and semi-arid China to date [ 64 ]. In this study, the version of the NWESMC was improved according to the national large-scale survey data in the first soil and water conservation survey [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the version of the NWESMC was improved according to the national large-scale survey data in the first soil and water conservation survey [ 38 ]. Abundant studies demonstrated that the RWEQ is capable of modeling daily, monthly, and annual (potential) wind erosion across field, regional, and global scales after some adjusting [ 32 , 64 , 65 ]. Here, we used the up-scaling method of RWEQ proposed by Guo [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, a series of conservation practices have been tested and developed across the globe for wind erosion control, including various conservation tillage and vegetation measures (Nordstrom & Hotta, 2004). Erosion experiments, including 137Cs tracing technique and wind tunnels, are the major methods for wind erosion rate quantification (Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%